"A new image of man": Harun Farocki and cinema as chiro-praxis. Issue 1 (1st January 2021) - Gustafsson, Henrik
ABSTRACT: In Harun Farocki's lifelong study of the mute language of manual expressions, the human hand is explored not only as a versatile tool, but as a repository of social memory, a topos in the genealogy of the moving image, and a critical agent in the theory and practice of filmmaking itself. While cinema distinguished itself from previous artistic media through its capacity to salvage and store everyday gestures for later scrutiny, accruing a Bilderschatz for future anthropological and archaeological research, it was also integral to an ongoing process that spurred the progressive withdrawal of the human hand from the manufacturing of images. By adopting a double-pronged approach that considers the programming of bodies and images as integrally aligned, the article traces the gradual demise of craftsmanship and the increasing automation of imaging and perception as engaged across a wide range of Farocki's essay films, found-footage compilations and observational documentaries. Taken together, this body of work at once proffers an encyclopedia of gesturing hands, a form of chiro-praxis in its own right, and a search for alternative or forgotten modes of manual communication and collective imagination. Graphical abstract: uf0001